Manipulação coerente de pontos quânticos em nanocavidades - Freitas Neto, Antonio de (2013)
In this work we studied the effects of coherent laser in a system formed by a quantum dot (QD) in a nanocavity. Initially we investigated the case where the energy of an éxciton are in resonance with the cavity mode and we vary the frequency of the laser. During our simulation we have used pulsed and continuos laser. We consider only the éxciton state of the QD, and in situations where both the laser and the cavity mode are close to resonance, allowing us to use the rotating wave approximation. The QD was treated as a two-level system and the cavity containing a maximum of four photons. For this study we used the Jaynes-Cummings model with an extra term related to the external pulse, which was used to manipulate quantum states. This was done with the help of diagonalization of the approximated Hamiltonian and searching for anticrossings in its energy spectrum. Then we use a continuous laser and the technique of calculating the average occupational each state to do a better mapping of the parameter values required to make the manipulation of quantum states. We found that the system can be manipulated using the process of two or more photons, and the energies of these photons could be estimated using a mapping procedure developed in this dissertation.